Seizure and Hepatosplenomegaly—Rare Manifestation of Parvovirus B-19: A Case Report and Review of the Literature - Yadav Kamlesh; Gupta Pallav; Murari Manjula; Malik Rohan (Journal of Tropical Medicine)
Parvovirus B19 is the etiologic agent of erythema infectiosum (fifth disease), a fever-rash illness occurring in childhood. We present a 10 month old child with high grade fever for 10 days, generalized tonic-clonic seizure, bilateral cervical lymphadenopathy, generalized maculopapular rash, hematemesis and malena. Bone marrow aspiration and liver biopsy were done. EBV serology and parvovirus PCR were also performed. Bone marrow aspiration and biopsy showed giant pro-erythroblast consistent with parvovirus infection. PCR showed amplification of parvovirus genomic sequences. Present case highlights an atypical presentation of Parvovirus B19 infection as fever, rash and hepatosplenomegaly.